Imitation of Cooperation in Prisoner's Dilemma Games with Some Local Interaction - Maarten C.W. Janssen (Tinbergen Institute, 2000)
In this paper I study conditions for the emergence of cooperativebehavior in a dynamic model of population interaction.The model has finitely many individuals located on a circle. The pay-off of each individual is partly based on the (local)interaction with neighbors and partly on (uniform) interaction withthe whole population. The dynamics is driven byimitative behavior. I show that for a large class of parameterscooperation will emerge if the population is large; if thepopulation is small, defection will prevail in the long run. Theresult contrasts with conventional wisdom which says that thelarger the population, the less likely cooperation will be.
Keywords: C72; D62; 330; Cooperation; Prisoner's Dilemma; Evolutionary Game Theory; Local Interaction; Gefangenendilemma; Theorie